2001
DOI: 10.4141/p00-043
|View full text |Cite
|
Sign up to set email alerts
|

CDC Milestone lentil

Abstract: CDC Milestone is a high-yielding, yellow cotyledon lentil (Lens culinaris Medik.) cultivar developed by the Crop Development Centre, Saskatoon, Saskatchewan. It is intended for cultivation in all lentil production areas of western Canada. CDC Milestone was evaluated for yield, resistance to ascochyta blight (Ascochyta lentis Vassilievsky) and agronomic performance as breeding line 512-2 in the Lentil Co-operative Yield Trials in 1995 and 1996. It has small seeds with pale green seed coat and is acceptable in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…The third population, LR-11, included 120 RILs developed from a cross between 'CDC Milestone' and 'ILL 8006-BM4'. 'CDC Milestone' is a high yielding, yellow cotyledon lentil cultivar developed at the CDC (Vandenberg et al 2001). 'ILL 8006-BM4' was derived from 'Barimasur-4', a highyielding, disease-resistant, red cotyledon cultivar from Bangladesh (Sarker et al 1999).…”
Section: Plant Materials and Phenotypingmentioning
confidence: 99%
“…The third population, LR-11, included 120 RILs developed from a cross between 'CDC Milestone' and 'ILL 8006-BM4'. 'CDC Milestone' is a high yielding, yellow cotyledon lentil cultivar developed at the CDC (Vandenberg et al 2001). 'ILL 8006-BM4' was derived from 'Barimasur-4', a highyielding, disease-resistant, red cotyledon cultivar from Bangladesh (Sarker et al 1999).…”
Section: Plant Materials and Phenotypingmentioning
confidence: 99%
“…The most environmentally acceptable and economically profitable method of control is to develop varieties with high levels of durable resistance. A few major ascochyta blight R-genes have been characterized in different lentil genotypes (Tay and Slinkard, 1989; Andrahennadi, 1994, 1997; Ahmad et al, 1997; Ford et al, 1999; Ye et al, 2000; Nguyen et al, 2001), and varieties partially resistant to ascochyta blight have been released (Ali, 1995; Vandenberg et al, 2001, 2002). …”
Section: Introductionmentioning
confidence: 99%
“…Crosses were made to introduce the resistance genes into lentil varieties with desirable agronomical traits (Buchwaldt et al, 1995). Genetic studies suggested that a single recessive gene conferred resistance in Indianhead, while that in PI 345629 and PI 320937 was based on single dominant resistance genes (Buchwaldt et al, 2001). The putative genes were designated lct-1 (Indianhead), LCT-2 (PI 320937) and LCT-3 (PI 345629).…”
Section: Sources Of Resistancementioning
confidence: 99%